Welcome to Scribd. Sign in or start your free trial to enjoy unlimited e-books, audiobooks & documents.Find out more
Standard view
Full view
of .

SPMZOOM–IN Form 4:Chapter 1Functions
SPMZOOM–IN Form 4:Chapter 5Indices and Logarithms
SPMZOOM–IN Form 4:Chapter 6Coordinate Geometry
SPMZOOM–IN Form 4:Chapter 7Statistics
SPMZOOM–IN Form 4:Chapter 8Circular Measure
SPMZOOM–IN Form 4:Chapter 9Differentiation
SPMZOOM–IN Form 4:Chapter 10Solution of Triangles
SPMZOOM–IN Form 4:Chapter 11Index Numbers
SPMZOOM–IN Form 5:Chapter 1Progressions
SPMZOOM–IN Form 5:Chapter 2Linear Law
SPMZOOM–IN Form 5:Chapter 3Integration
SPMZOOM–IN Form 5:Chapter 4Vectors
SPMZOOM–IN Form 5:Chapter 5Trigonometric Functions
SPMZOOM–IN Form 5:Chapter 6Permutations and Combinations
SPMZOOM–IN Form 5:Chapter 7Probability
SPMZOOM–IN Form 5:Chapter 8Probability Distributions
SPMZOOM–IN Form 5:Chapter 9Motion Along a Straight Line
SPMZOOM–IN Form 5:Chapter 10Motion Along a Straight Line
0 of .
Results for:
P. 1
Nota Matematik Tambahan Tingkatan 4 Dan 5 SPM

# Nota Matematik Tambahan Tingkatan 4 Dan 5 SPM

Ratings: (0)|Views: 5,586|Likes:
SPM ZOOM–IN Form 4: Chapter 1 Functions
Paper 1 1. The relation in the given graph can be represented using the following arrow diagram.
A 1 2 3 4 B 10 20 30 40

4. (a) gf : x → x2 + 6x + 2 gf (x) = x2 + 6x + 2 g(x + 4) = x2 + 6x + 2 Let x + 4 = u x=u–4 g(u) = (u – 4)2 + 6(u – 4) + 2 = u2 – 8u + 16 + 6u – 24 + 2 = u2 – 2u – 6 ∴ g(x) = x2 – 2x – 6 (b) fg(4) = f 42 – 2(4) – 6 = f(2) =2+4 =6 5. Let g–1(x) = y g(y) = x 3y + k = x x–k y= 3 1 k y = x– 3 3 1 k ∴ g–1(x) = x – 3 3 It is given that g–1(x)
SPM ZOOM–IN Form 4: Chapter 1 Functions
Paper 1 1. The relation in the given graph can be represented using the following arrow diagram.
A 1 2 3 4 B 10 20 30 40

4. (a) gf : x → x2 + 6x + 2 gf (x) = x2 + 6x + 2 g(x + 4) = x2 + 6x + 2 Let x + 4 = u x=u–4 g(u) = (u – 4)2 + 6(u – 4) + 2 = u2 – 8u + 16 + 6u – 24 + 2 = u2 – 2u – 6 ∴ g(x) = x2 – 2x – 6 (b) fg(4) = f 42 – 2(4) – 6 = f(2) =2+4 =6 5. Let g–1(x) = y g(y) = x 3y + k = x x–k y= 3 1 k y = x– 3 3 1 k ∴ g–1(x) = x – 3 3 It is given that g–1(x)

### Availability:

See more
See less

05/25/2013

pdf

text

original

Pages 5 to 40 are not shown in this preview.